2016
DOI: 10.1038/srep37945
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide triggers a transient metabolic reprogramming in Arabidopsis

Abstract: Nitric oxide (NO) regulates plant growth and development as well as responses to stress that enhanced its endogenous production. Arabidopsis plants exposed to a pulse of exogenous NO gas were used for untargeted global metabolomic analyses thus allowing the identification of metabolic processes affected by NO. At early time points after treatment, NO scavenged superoxide anion and induced the nitration and the S-nitrosylation of proteins. These events preceded an extensive though transient metabolic reprogramm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 60 publications
3
62
0
Order By: Relevance
“…Regulation of amino-acid levels could participate in signaling and production of other metabolites [53], including polyamines. León et al [54] observed extensive metabolic and transient reprogramming 6 h after treatment with NO in Arabidopsis thaliana (L.) Heynh, including increased polyamines levels that are considered good indicators of NO activation processes, dedicated to remedy oxidative stress and regulate plant growth and development. A second hypothesis may be associated not with decreased synthesis of these amino acids, but with reduction of protein degradation, resulting in lower concentrations of free amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of amino-acid levels could participate in signaling and production of other metabolites [53], including polyamines. León et al [54] observed extensive metabolic and transient reprogramming 6 h after treatment with NO in Arabidopsis thaliana (L.) Heynh, including increased polyamines levels that are considered good indicators of NO activation processes, dedicated to remedy oxidative stress and regulate plant growth and development. A second hypothesis may be associated not with decreased synthesis of these amino acids, but with reduction of protein degradation, resulting in lower concentrations of free amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, chemically blocking the hypoxia-induced NO burst at the onset of hypoxia strongly impaired hypoxia survival in maize root tips (Mugnai et al, 2012). In addition to its role in regulating ERFVII abundance, NO also may exert a regulatory role during flooding or hypoxia, by posttranslational modification of proteins via S-or metal-nitrosylation and Tyr nitration (for review, see Astier et al, 2011;León et al, 2016). Exogenous NO application in Arabidopsis effectively S-nitrosylated proteins involved in respiration, metabolism, signaling, and stress responses (Lindermayr et al, 2005;Astier et al, 2011;León et al, 2016).…”
Section: The Functional Role Of Nomentioning
confidence: 99%
“…In addition to its role in regulating ERFVII abundance, NO also may exert a regulatory role during flooding or hypoxia, by posttranslational modification of proteins via S-or metal-nitrosylation and Tyr nitration (for review, see Astier et al, 2011;León et al, 2016). Exogenous NO application in Arabidopsis effectively S-nitrosylated proteins involved in respiration, metabolism, signaling, and stress responses (Lindermayr et al, 2005;Astier et al, 2011;León et al, 2016). S-Nitrosylated proteins potentially involved in flooding signaling and adaptation include ERFVIIs, cytochrome c oxidase (COX), aconitase, phytoglobins, and the H 2 O 2 scavenger APX1 (Millar and Day, 1996;Perazzolli et al, 2004;Gupta et al, 2012;Gibbs et al, 2014;Begara-Morales et al, 2016).…”
Section: The Functional Role Of Nomentioning
confidence: 99%
“…S‐nitrosylation modifications led to a decrease in cellular glycolysis enzymes, ATP synthase activities, content of acetyl coenzyme A, ATP, ADP‐glucose and UDP‐glucose, which all together eventually inhibited polysaccharide‐biosynthesis and caused monosaccharide accumulation (Zhang et al, ). Accordingly, NO‐treated plants displayed less starch granules and increased sugar content (León, Costa, & Castillo, ). Regarding another primary metabolic pathway, nitrate assimilation seems to be also controlled by NO through negative transcriptional regulation on NR and high affinity nitrate transporter encoding genes in wheat (Adavi & Sathee, ), a process that seems to be dependent on the N compound source (Balotf et al, ).…”
Section: No As a Regulator Of Development And Stress‐related Responsesmentioning
confidence: 99%